Moderating Effect Of Profitability In Disclosure Of Corporate Social Responsibility, Leverage, And Firm Size: Effect On Share Price - Annisa Kurniawan; Nanda Wahyu Indah Kirana (UNIVED Press, 2024)
This research aims to examine the effect of Corporate Social Responsibility (CSR), leverage, and firm size on share prices in companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX), with profitability as a moderating variable. This research uses a quantitative approach with a sample size of 20 companies over 7 years, namely 140 research samples obtained using a purposive sampling technique. This research uses secondary data collected through documentation method. The data analysis technique used is Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0 software. The test stages using PLS-SEM are divided into 3 stages, namely measurement model analysis (outer model), structural model analysis (inner model), and hypothesis testing. The results of the analysis in this study indicate that CSR disclosure, leverage, firm size and profitability influence the share prices of LQ45 index companies. Apart from that, profitability is unable to moderate the influence of CSR and leverage on the share prices of LQ45 index companies. However, profitability is able to moderate the influence of firm size on the share prices of LQ45 index companies.